Robotic Partial Cystectomy for Urachal Carcinoma: A Case Report and Review of the Literature - Rawad Abou Zahr; Valentin Colinet; Aurore Mattlet; Teddy Jabbour; Romain Diamand (Case Reports in Urology)
Urachal carcinoma is a very rare tumor, commonly found in the urachal remnant connecting the bladder dome to the umbilicus. Diagnosis is often challenging due to the location of the tumor and its late presentation. We hereby report the case of a 49-year-old female where the diagnosis of urachal carcinoma was made and a robotic partial cystectomy associated with en bloc resection of the umbilicus was performed. We aim to present the clinical aspects, presentation, and diagnosis of this rare entity along with a review of the literature.